Assessment of Current Russian Practices in Urban Development Strategies Elaboration - Anastasiya CHICHERINA; Igor RISIN (Communications of International Proceedings, 2020)
Since 2007, more than half of the world’s population has lived in urban areas and it is estimated that the proportion will exceed 68 per cent by 2050. Cities are faced many challenges related to environmental degradation, globalization, inequalities, social segregation etc. Urban strategy is increasing in importance as a tool that guide the city development. The objective of this research is to produce an assessment of the current Russian practices of urban socioeconomic development strategies preparation and elaboration. This research will suggest results of the content analysis of the municipal strategies elaborated in compliance with the requirements of Federal Law No. 172 “On strategic planning in the Russian Federation” and comparative review of methodological approaches to addressing the key tasks of strategic planning. These challenges are related to measuring the achievement of previously set goals, determining the competitive advantages of the city, substantiating the strategic goals for urban development and identifying core strategic indicators. The empirical basis is formed by the official strategies of the following cities: Voronezh, Kazan, Kaliningrad, Magnitogorsk, Penza, Rostov-on-Don, Tver, Tolyatti and Ulan-Ude. The research identified widespread deficiencies in urban strategic planning and diagnosed the main causes of their occurrence and persistence.
Keywords: urban development strategy; key tasks and approaches of strategic planning